Changing in chemical and physical attributes of a sandy soil under irrigated mango cultivation in semiarid region - Lima, Augusto Miguel N.; Cardoso, José Alberto Ferreira; Cunha, Tony Jarbas Ferreira; Rodrigues, Marcos Sales; Hernani, Luis Carlos; Cunha, Jailson Cavalcante; Amaral, Andre Julio do; Neto, Manoel Batista de Oliveira (Comunicata Scientiae, 2018)
Accelerated land use changes have been observed in Brazil. In Northeast, the Caatinga (native vegetation) has been replaced by fruit production, especially by mango and grapevine cultivation. Land use changes, tied to management techniques, can change the soil chemical and physical attributes. Thus, the present study aimed to evaluate the impact of irrigated mango cultivation in soil chemical and physical attributes in relation to the native Caatinga in the semi-arid region. The study was carried out at Boa Esperança Farm located in Petrolina, Pernambuco State, Brazil. In areas under irrigated mango and native Caatinga soil samples at 0-10 and 10-20 cm depth were collected. After collected and prepared soil samples, it was determined the macro (Ca2+, Mg2+, K+, P) and micronutrients (Cu2+, Fe2+, Zn2+, Mn2+) contents, Na content, electrical conductivity, pH, exchangeable acidity (Al3+) and potential acidity (H+Al). It was also determined soil texture, bulk density, particle density and total porosity. The mango cultivation increased the macronutrient contents, as well as, the micronutrients except for Fe2+ content. The physical attributes did not show difference comparing irrigated mango to native caatinga.